Economicaly Based CRT Sampling Inspection Plans - Vaišvila, A. (Elektronika ir Elektrotechnika, 2003)
Quality losses function model for final inspection is made evaluating: probability characteristics of the production flow ininspection, final inspection flows scheme, production classification mistakes, sampling inspection and 100 % inspection reinspectionaverage costs, costs for the defected product rework, losses for reclamated production from customers. Quality losses function values arecalculated using probability modeling and various inspections plans as well as origin restrictions and economically optimal samplinginspection plans parameters minimizing losses in developed. Ill. 4, bibl. 8 (in Lithuanian; summaries in Lithuanian, English, Russian).